2009
DOI: 10.3390/molecules14010191
|View full text |Cite
|
Sign up to set email alerts
|

Pimarane-type Diterpenes: Antimicrobial Activity against Oral Pathogens

Abstract: Seven pimarane type-diterpenes re-isolated from Viguiera arenaria Baker and two semi-synthetic pimarane derivatives were evaluated in vitro against the following main microorganisms responsible for dental caries: Streptococcus salivarius, S. sobrinus, S. mutans, S. mitis, S. sanguinis and Lactobacillus casei. The compounds ent-pimara-8(14),15-dien-19-oic acid (PA); ent-8(14),15-pimaradien-3b-ol; ent-15-pimarene-8b,19-diol; ent-8(14),15-pimaradien-3b-acetoxy and the sodium salt derivative of PA were the most ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 27 publications
5
87
0
3
Order By: Relevance
“…However, various adverse effects such as tooth and restoration staining, increased calculus formation, diarrhea, and disarrangements of the oral and intestinal flora have been associated with the use of these chemicals (Chung et al 2006, More et al 2008. These drawbacks justify the search for new effective anticariogenic compounds that could aid caries prevention (Porto et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…However, various adverse effects such as tooth and restoration staining, increased calculus formation, diarrhea, and disarrangements of the oral and intestinal flora have been associated with the use of these chemicals (Chung et al 2006, More et al 2008. These drawbacks justify the search for new effective anticariogenic compounds that could aid caries prevention (Porto et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…The MICs of the samples against the test bacterial strains were performed according to the broth microdilution method. The entire procedure was performed in a laminar flow hood, with all of the glassware, pipette tips, culture media and 96-well microplates sterilised (Porto et al, 2009;Carvalho et al, 2011). Samples were dissolved in 1 mg ml -1 dimethyl sulphoxide (DMSO), followed by dilution in tryptic soy broth (Difco) for aerobic and Schaedler broth (Difco) supplemented with haemin (5 μg ml −1 ) and vitamin K1 (10 μg ml −1 ) for anaerobic; concentrations ranged from 400 to 10 µg ml -1 .…”
Section: Minimum Inhibitory Concentration (Mic): Broth Microdilution mentioning
confidence: 99%
“…Diterpenes also display significant antimicrobial activity (Tatsimo et al, 2005;Kuzma et al, 2007;Ndi et al, 2007;Fukumoto et al, 2008;Porto et al, 2009a;Porto et al, 2009b;Carvalho et al, 2011;Andrade et al, 2011;Moreira et al, 2016;Moreti et al, 2017;Veneziani et al, 2017). Ambrosio et al (2004) isolated and identified diterpenes of the pimarane type from V. arenaria baker root extracts.…”
Section: Introductionmentioning
confidence: 99%